(untitled) (Research, Society and Development, 2022)
This study aims to identify ways to transfer technology and technological innovation that contribute to the development of rural producers. The proposal is being developed by the Postgraduate Program in Biotechnology and Environmental Monitoring, Federal University of São Carlos, Campus Sorocaba, State of São Paulo, Brazil. The procedures used in this work are characterized as interdisciplinary, bibliographical, qualitative, descriptive and multiple case studies. Technology transfer through events, generation of patents for public domain, product generation and software registration were analyzed for transfer purposes through technical training and technology transfer contract to rural producers carried out in the Project: "Management of technologies generated in sugarcane expansion projects and their environmental effects" counting on the support of the São Paulo State Research Support Foundation in Process: 2017/18918-5. Through the results obtained, it can be inferred that these practices are effective, mainly through digital media, to rural producers, which affirms the need to encourage these technology transfer processes. Furthermore, this article demonstrates how researchers can maximize production benefiting society.